Within the imaginaries : writings of resistance : an exegesis presented in partial fulfilment of the requirements for the postgraduate degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Thomas, Ilish (Massey University, 2022)
What change can emerge from within the margins? The possibilities can be both limited and endless. I explore the notion that political-imaginaries can foster change; what can be created with limitations can hold power unique to other circumstances. This exegesis details my practice which engages images of ‘in-betweenness’, resistance, strategies of mediation and cultural navigation from the perspective of a person of South Asian descent in Aotearoa, New Zealand. It will cover various tensions, expectations, responsibilities and roles of the artist in the contemporary art context of Aotearoa. I will draw upon common perceptions of “everyday life” in ways that complicate social norms and engender new-political-imaginaries. My intention is to examine the experience as a settler of the South Asian diaspora in the South Pacific. This is a reflection of how I move through the world, aligning with and/or contrasting world views with those around me of various standing points. Black cultural theorist Bell Hooks, identifies the potential for a position of strength within social and cultural margins. For Hooks, moments of intimacy, nuance, and the monotony of the everyday can foster spaces of autonomy and agency. By threading discussions by Hooks and the likes of Lana lopesi and Moana Jackson, I will share my exploration and findings within my creative research practice.
Keywords: 360604 Photography, video and lens-based practice